IgGFc-binding protein in pregnancies complicated by spontaneous preterm delivery: a retrospective cohort study - Stranik, Jaroslav; Kacerovsky, Marian; Soucek, Ondrej; Kolackova, Martina; Musilova, Ivana; Pliskova, Lenka; Bolehovska, Radka; Bostik, Pavel; Matulova, Jana; Jacobsson, Bo; Andrys, Ctirad (Scientific reports, 2021)
To determine the IgGFc-binding protein (FcgammaBP) concentration in amniotic and cervical fluids in preterm prelabor rupture of membranes (PPROM) and preterm labor with intact membranes (PTL) and to assess the diagnostic indices of FcgammaBP to predict intra-amniotic infection (the presence of both microbial invasion of the amniotic cavity and intra-amniotic inflammation). In this study, we included 170 and 79 women with PPROM and PTL, respectively. Paired cervical and amniotic fluid samples were obtained using a Dacron polyester swab and transabdominal amniocentesis, respectively. The FcgammaBP concentrations in the samples were assessed using an enzyme-linked immunosorbent assay. The presence of intra-amniotic infection was associated with elevated FcgammaBP concentrations in pregnancies with PPROM and PTL [PPROM-presence: 86 ng/mL vs. absence: 13 ng/mL, p < 0.0001, area under receiver operating characteristic curve (AUC) = 0.94; PTL-presence: 140 ng/mL vs. absence: 22 ng/mL, p < 0.0001, AUC = 0.86]. In cervical fluid, the concentrations of FcgammaBP were elevated in the presence of intra-amniotic infection in pregnancies with PPROM only (presence: 345 ng/mL vs. absence: 60 ng/mL, p < 0.0001, AUC = 0.93). FcgammaBP in amniotic fluid might be a marker of intra-amniotic infection in women with both PPROM and PTL However, in cervical fluid, it is only observed in women with PPROM.
Keywords: Cell Adhesion Molecules; plodová voda; biologické markery; retrospektivní studie; Biomarkers; infekční komplikace v těhotenství; předčasný porod; Pregnancy; molekuly buněčné adheze; těhotenství; Adult; dospělí; Premature Birth; Amniotic Fluid; lidé; ženské pohlaví; Humans; Pregnancy Complications, Infectious; Retrospective Studies; Female